A comparison of portal venous versus systemic venous drainage in pancreas transplantation. Issue 2 (February 2019) - Siskind, Eric; Amodu, Leo; Liu, Chang; Akerman, Meredith; Stodghill, Joshua; Wali, Ravinder; Piper, James; Jonsson, Johann; Molmenti, Ernesto; Ortiz, Jorge
Abstract: Background: The decision to utilize portal or systemic venous drainage in pancreas transplantation is surgeon- and center-dependent. Information regarding the superior method is based on single-center reports and animal models. Methods: UNOS data on adults receiving pancreas and kidney-pancreas transplants from 1987 to 2016 were analyzed (n = 29 078). The groups analyzed were: systemic venous pancreas graft drainage (SVD, n = 24 512) or portal venous pancreas graft drainage (PVD, n = 4566). A Cox proportional hazard model compared patient and allograft survival between groups. Results: No statistically significant differences were observed for patient and allograft survival at 1, 3, 5, 10, or 15 years post-transplant at each time interval and cumulatively (patient – HR:1.041; 95% CI:0.989–1.095; allograft – HR:0.951; 95% CI:0.881–1.027). PVD reduced the risk of death by 22.0% (P = 0.017) compared to SVD for patients undergoing pancreas after kidney transplant (PAK); no statistically significant difference was found for patients undergoing other types of transplants. Conclusion: There is no significant clinical difference in patient or allograft survival between PVD and SVD in pancreas transplantation for the majority of patients. For the subgroup of PAK, PVD was associated with decreased mortality. For individual surgeons, center and patient scenarios should dictate which technique is performed.